EFEKTIVITAS PENGGUNAAN APLIKASI QUIZIZZ DALAM EVALUASI PEMBELAJARAN DARING ILMU PENGETAHUAN ALAM (IPA) MATERI MACAM-MACAM GAYA KELAS IV MI AL IHSAN DAMARSI - Wahyu Maulida Lestari; M. As Ari Abd Rohman (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study aims to determine the effectiveness of the use of the quizizz application in evaluating online learning of Natural Sciences (IPA) on various styles of material for class IV MI Al Ihsan Damarsi. The research conducted in this research is quantitative research. Data collection techniques in this study were tests and item validity. While the validation in this study is a test sheet and a question validation sheet. Based on the validation results obtained from the validator, it shows that the 0.702 validation test results are categorized as valid. The results of the reliability test in this study have a value of 0.883 which means that the value is very high and can be used. Normality test results 0.200 > 0.05 in the normal sense that it can still be used and the last is the homogeneity test results in this study, namely 0.947 > 0.05. So it can be concluded that the data is homogeneous. The results of the research and discussion can be concluded that there is an effect of using the Quizizz Application on the effectiveness of the evaluation of science learning with a Tcount of 13.578 > T table of 2.086 and a significance value of 0.000 < 0.05.